Surgical Management of Rectal Prolapse in Infants and Children - Saadai, Payam; Trappey, A. Francois; Langer, Jacob L. (European Journal of Pediatric Surgery, 2020)
The surgical management of children with rectal prolapse is wide ranging and without consensus within the pediatric surgical community. While the majority of rectal prolapse in infants and children resolves spontaneously or with the medical management of constipation, a small but significant subset of patients may require intervention for persistent symptoms. In this review, we discuss the etiology and pathophysiology of rectal prolapse in both infants and children, options for medical management, described interventions and surgical options and their outcomes, and future avenues for research and investigation.
Keywords: rectal prolapse; rectopexy; sclerotherapy; constipation; cystic fibrosis